CREATIVITY OF FUTURE TECHNOLOGY TEACHERS CREATIVE TECHNOLOGIES OF DEVELOPMENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The article describes the issues of creativity formation of future teachers of technology in the process of teaching specialized subjects. This article describes the improvement of the new creative technologies introduced in our country in the educational system.The article describes the issues of creativity formation of future teachers of technology in the process of teaching specialized subjects. This article describes the improvement of the new creative technologies introduced in the educational system in our country.